Una nueva especie de Physalis (Solanaceae) de Querétaro, México - Martinez, Mahinda; Hernandez, Luis (Instituto de Ecología, A.C., 1999)
Physalis queretaroensis, a scarce plant restricted to the municipality of Landa de Matamoros, is described. The species is related to P. volubilis Waterf., from which it differs in the form and insertion of the leaves and vestiture.